Disciplining Children in Hadith: A Normative Study and Its Relevance to Modern Education - Muhammad Ghaffar Arafat Abdul Azmi; Romlah Abubakar Askar; Miftahuddin M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research aims to explore the methodology of child discipline in Hadith through a normative study and analyze its relevance within the context of modern education. Employing a library research method with a descriptive-analytical qualitative approach, this study focuses on the thoughts of Muhammad Nur Abdul Hafidz Suwaid in the book Manhaj At-Tarbiyah An-Nabawiyah lil Tifl. The findings indicate that the Prophetic discipline model begins with a thorough diagnosis of the root causes of a child's mistake, categorized into intellectual, practical, and personal factors. The primary methodology prioritizes non-physical approaches through intellectual correction (at-tashih al-fikri) and practical guidance (at-tashih al-amali). Physical sanctions are positioned only as a last resort (ultimum remedium), strictly governed by ethical boundaries such as the prohibition of hitting before the age of ten, the prohibition of hitting the face, and the obligation to cease sanctions if the child seeks protection in the name of Allah. This study concludes that discipline in Islam is a manifestation of compassion (rahmah) aimed at fostering internal awareness rather than mere outward compliance. This model remains highly relevant to modern pedagogical principles as it emphasizes the protection of a child’s dignity and the prevention of violence in educational settings.